Extension Program on the Utilization of Cow Urine Waste into Biourine with the Addition of Pineapple Peel Bioactivator in Sumberpitu Village, Pasuruan Regency - Manek, Petrus; Gunawan, Gunawan; Wandansari, Niken Rani (Journal of Agriprecision & Social Impact, 2024)
Agriculture is one of the main business sectors used as the livelihood of the people of Sumberpitu village with dairy farming as an accompanying business unit. However, from the existing potential, there are several problems such as steps and expensive inorganic fertilizers. From the results of deepening the problem through interviews, it shows that farmers in Sumberpitu Village do not have any knowledge and skills to use cow urine as liquid organic fertilizer in their farming business. The purpose of this study is to conduct extension program on the use of cow urine waste as biourine with the addition of pineapple skin bioactivators and analyze behavior changes in aspects of knowledge, attitudes and skills of farmers in Sumberpitu village. The research method used in this study is the Level III action research method. The evaluation results show that extension services can increase farmers' knowledge from a percentage of pre-test scores of 50% to 82% in post-test scores, which can be categorized as very high. In the aspect of attitude, the percentage of pre-test scores of 48% increased to 76% in post-test scores and was included in the high category so as to show a positive attitude towards the extension program material delivered. While in the aspect of presentation skills, the post test score is 83%, which can be categorized as “very high”. These results show that the extension program provided has proven effective in changing farmer behavior in increasing knowledge and attitudes as well as developing farmers' skills in utilizing cow urine waste as biourine with the addition of pineapple peel as a bioactivator.